Selection of Optimal Tobacco Cessation Medication Treatment in Patients With Cancer - Wippold, Rosario (Clin J Oncol Nurs, 2015)
BACKGROUND: Tobacco use is responsible for almost half a million deaths per year in the United States, and it accounts for one-third of all cancer deaths. Limited data concerning tobacco treatment among patients with cancer are available. In addition, these patients often have complicated medical histories and are taking multiple medications. No clear, published procedures exist to help the healthcare provider select the proper medication for tobacco cessation in that context. OBJECTIVES: This article describes the screening process established within the Tobacco Treatment Program (TTP) at the University of Texas MD Anderson Cancer Center to minimize the risk of prescribing a contraindicated tobacco cessation medication to patients with cancer. The screening process developed and used by the TTP is presented as a viable model for selecting appropriate tobacco cessation medications for patients with cancer. METHODS: The electronic medical record of each patient who uses tobacco is carefully reviewed once he or she is scheduled for a consultation. A summary is produced with a standardized template and used later as a template for the medical provider evaluation. Precautions are put in place with consideration of the characteristics of each of the tobacco cessation medications (e.g., mechanism of action, route of administration, interactions with other medications, possible side effects, contraindications). Since 2006, the TTP has had more than 4,000 new patients and more than 39,000 follow-up visits. FINDINGS: Because each patient with cancer has unique medical, psychological, and social circumstances, the process of selecting the optimal tobacco cessation medication needs to be individualized. Oncology healthcare providers should follow some form of screening to tailor a medication plan to each patient.